From Ideas to Action Transforming Learning to Inspire Action on Critical Global Issues - Gibson, Heidi (Open Monographs, 2021)
Transforming learning from a passive to an active endeavor is critically important in today's world. In 2015, the United Nations identified seventeen Sustainable Development Goals that represent a global consensus on the world's most pressing issues. Realizing these ambitious goals will require concerted action at all levels, including local action. Young people are valuable components of this, and their learning experiences should both inform and inspire them as current and future changemakers. From Ideas to Action articulates the theoretical basis of Smithsonian Science for Global Goals, a series of socio-scientific community research guides focused on achieving a systemic understanding of global problems with the goal of inspiring young people to take informed and sustained action to help address global issues.